Seasonal adjustment of leaf embolism resistance and its importance for hydraulic safety in deciduous trees. Issue 5 (5th October 2022) - Sorek, Yonatan; Greenstein, Smadar; Hochberg, Uri
Abstract: Embolism resistance is often viewed as seasonally stable. Here we examined the seasonality in the leaf xylem vulnerability curve (VC) and turgor loss point (ΨTLP ) of nine deciduous species that originated from Mediterranean, temperate, tropical, or sub‐tropical habitats and were growing on the Volcani campus, Israel. All four Mediterranean/temperate species exhibited a shift of their VC to lower xylem pressures (Ψx ) along the dry season, in addition to two of the five tropical/sub‐tropical species. In three of the species that exhibited VC seasonality, it was critical for avoiding embolism in the leaf. In total, seven out of the nine species avoided embolism. The seasonal VC adjustment was over two times higher as compared with the seasonal adjustment of ΨTLP, resulting in improved hydraulic safety as the season progressed. The results suggest that seasonality in the leaf xylem vulnerability is common in species that originate from Mediterranean or temperate habitats that have large seasonal environmental changes. This seasonality is advantageous because it enables a gradual seasonal reduction in the Ψx without increasing the danger of embolism. The results also highlight that measuring the minimal Ψx and the VC at different times can lead to erroneous estimations of the hydraulic safety margins. Changing the current hydraulic dogma into a seasonal dynamic in the vulnerability of the xylem itself should enable physiologists to understand plants' responses to their environment better.